The Influence of Ice Breaking Strategy on Student Learning Interest in Christian Religious Education: A Study at SD Negeri 175761 Pulo Pakpahan, North Tapanuli Regency - Siltuanus Simanungkalit; Dorlan Naibaho; Julita Herawati P; Ronny Simatupang; Maryska Debora Silalahi (Journal of Religious and Socio-Cultural, 2026)
This research aims to determine the positive and significant influence of the Ice Breaking strategy by Christian Religious Education (CRE) teachers on the learning interest of fourth-grade students at SD Negeri No 175761 Pulo Pakpahan, Pangaribuan District, North Tapanuli Regency, in the 2025/2026 academic year. The study employed a quantitative method with descriptive analysis. The population consisted of 161 Protestant Christian students, with a sample of 30 fourth-grade students selected through purposive sampling. Data were collected using a closed questionnaire consisting of 30 items (16 items for variable X and 14 items for variable Y), which had been tested for validity and reliability. The results showed a positive and significant influence between Ice Breaking strategies and student learning interest, evidenced by correlation coefficient rxy = 0.587, t-test value = 3.805, regression equation Ŷ = 26.92 + 0.38X, and determination coefficient of 34.4%. The F-test value of 14.73 exceeded the F-table value of 1.62 at α=0.05, indicating that the alternative hypothesis is accepted. This research confirms that Ice Breaking strategies significantly contribute to enhancing student learning interest in Christian Religious Education. The findings imply that CRE teachers should consider implementing structured Ice Breaking activities as an effective pedagogical strategy to create conducive learning environments and foster student engagement.